P428Cost-effectiveness of sedation for electrical cardioversion in the emergency department: a subanalysis of the Instead trial. (18th June 2020) - Stronati, G; Ricciotti, J; Cipolletta, L; Belfioretti, L; Capucci, A; Dello Russo, A; Guerra, F
Abstract: BACKGROUND Direct current cardioversion (DCCV) represents the most widely used and effective method to restore sinus rhythm in patients with persistent AF. No specific guidelines or recommendations with regards to the most appropriate drug that should be used for procedural sedation have been described. Propofol is one of the most used drugs, however it should be administered only by personnel trained in advanced airway management. Midazolam has been described as a potential alternative. PURPOSOSE The aim of our study was to assess the cost-effectiveness of procedural sedation with midazolam compared to the one with propofol for urgent/emergency DCCV in the emergency department. METHODS Single centre, prospective, open blinded, randomized study including 66 consecutive patients admitted to the emergency department requiring urgent or emergency DCCV for haemodynamic instability, chest pain or symptomatic palpitations. The enrolled patients were randomized in a 1:1 fashion into the propofol or midazolam group. With regards to the propofol group, the procedure was carried out with the assistance of the anaesthesiologist. In the midazolam group, both the procedural sedation and the cardioversion were carried out by the cardiologist alone. RESULTS Thirty-tree patients underwent procedural sedation with propofol and 33 with midazolam. Medical costs included expenses for personnel and related to possible procedural delays. The median medical cost was of 14.9 € for the midazolam group and 46.7 € for the propofol group (p<.001) and was mainly driven by an increased delay and lack of coordination between the cardiologist and the anaesthesiologist. The median material cost in the midazolam group was higher than in the propofol one as the former implied the use of flumazenil (83.7 € vs. 78.8 €, p<.001). Hospitalization costs included the cost related to monitoring time in the emergency department and possible costs derived by the admission to a medical ward. They added up to a median of 28.1 € in the midazolam group and 48.7 for the propofol group (p=.004) as most patients were discharged safely after a few hours. The total median cost of urgent/emergency DCCV with midazolam was estimated to be 126.2 € (1st-3rd quartiles 114.4-142.6) and 203.3 € (1st-3rd quartiles 149.3-734.8) with propofol (p<.001). There was no significant difference in terms of adverse events. Sedation with midazolam was as safe, efficient and tolerated as sedation with propofol. Length of procedure was shorter when midazolam was used compared to propofol usage. Patients who underwent sedation with midazolam were safely discharged earlier. CONCLUSIONS Procedural sedation for electrical cardioversion in the emergency department is more cost-effective than sedation with propofol. By using midazolam we estimated that 77 € are saved for each DCCV. This is driven by the absence of another operator and the possibility of a quicker discharge given the use of flumazenil.